Konsep Pendidikan Agama Islam Multikultural Dalam Turats Ta’limul Muta’alim Syekh Al Zarnuji - Sodri, Imam; Uma, Diki Sifaul (Edification Journal : Pendidikan Agama Islam, 2025)
Islamic religious education plays an important role in shaping the character and morality of individuals and society. Multiculturalism is inseparable from the diverse nature of life. One of the classic works frequently referenced in the field of Islamic education is Ta'limul Muta'alim by Sheikh Az-Zarnuji. This work contains guidelines and ethics for seekers of knowledge, covering moral values and proper conduct in learning. In the context of an increasingly multicultural society, it is crucial to explore how the educational concepts in Ta'limul Muta'alim can be adapted to support cultural and religious diversity. This research aims to examine the Islamic educational values in Ta'limul Muta'alim that are relevant to multicultural education. The study employs a literature review and text analysis method. The findings show that Sheikh Az-Zarnuji emphasizes the importance of tolerance, respect for differences, and the significance of ethics in the educational process, which align closely with the principles of multicultural education. The method reflected in this classical work is a contributive method, with an aesthetic approach and a dimension focused on the process of knowledge construction.